Splitting the Tactical Vote? Coordination Problems with Polling Model‐Driven Tactical Voting Websites. Issue 1 (4th March 2020) - Nicholls, Tom; Hayton, Richard
Abstract: The 2019 general election gave prominence to tactical voting advice websites, particularly those projecting constituency‐level results using national polling data and sophisticated multi‐level regression and poststratification (MRP) polling models. We see tactical voting as an example of a coordination game and argue that polling‐model driven advice websites are disruptive to the existing focal points for strategic voting. Although such websites may well help identify the strongest candidate based on constituency demographics, the article argues they are unlikely to coalesce support behind that single candidate, a prerequisite for successful tactical voting. In practice, there are multiple competing models and websites as well as other key sources of information to voters. Furthermore, the heuristic of relying on tactical voting websites is vulnerable to strategic action by partisans. In short, it is argued that the emergence of these websites risks muddying the waters further for electors seeking to vote tactically, potentially splitting the tactical vote rather than unifying it.